1989
DOI: 10.3758/bf03208071
|View full text |Cite
|
Sign up to set email alerts
|

Manual discrimination and identification of length by the finger-span method

Abstract: Experiments were conducted on length resolution for objects held between the thumb and forefinger. The just noticeable difference in length measured in discrimination experiments is roughly 1 mm for reference lengths of 10 to 20 mm. It increases monotonically with reference length but violates Weber's law. Also, it decreases when the subject is permitted to maintain a constant finger span between trials; however, it tends to increase when the nondominant hand is used. As would be expected from studies of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 21 publications
5
53
4
Order By: Relevance
“…This is the second in a series of papers concerned with the manual perception of objects, and, more specifically, with the ability to distinguish between different objects manually (i.e., with manual resolution). In the first paper, we reported the results of a variety of experiments in which the subject was required to discriminate or identify object length by means of the finger-span method (Durlach et al, 1989). In these experiments, a rigid object was grasped between the terminal pads of the thumb and forefinger, and object length was estimated by sensing the differential position of these pads.…”
mentioning
confidence: 99%
“…This is the second in a series of papers concerned with the manual perception of objects, and, more specifically, with the ability to distinguish between different objects manually (i.e., with manual resolution). In the first paper, we reported the results of a variety of experiments in which the subject was required to discriminate or identify object length by means of the finger-span method (Durlach et al, 1989). In these experiments, a rigid object was grasped between the terminal pads of the thumb and forefinger, and object length was estimated by sensing the differential position of these pads.…”
mentioning
confidence: 99%
“…Furthermore, the discrimination thresholds increased by a factor ofabout two under conditions ofvarying contact lengths. Durlach et al (1989) and Tan, Pang, and Durlach (1992) investigated haptic length perception and did not find systematic oyerestimations or underestimations for length perception by means ofthe finger-span method. However, it is quite difficult to extrapolate their results to ours, because the manner in which the stimuli were touched and their experimental task were different.…”
mentioning
confidence: 99%
“…This is the third in a series ofpapers concerned with how individual physical properties of objects are perceived. In the first paper of this series (Durlach et al, 1989), we reported the results ofa variety ofexperiments in which the subject was required to discriminate or identify object length (related to the variable x) by means of the fingerspan method. The just noticeable difference (JND) in length measured in discrimination experiments was roughly 1 rom for reference lengths of 10-20 rom, and increased to roughly 2.2 rom for a reference length of80 rom.…”
mentioning
confidence: 99%